Beneficiation of Eskişehir Beylikova Bastnasite Ore and Rare Earth Elements Recovery - Gulsah Turker; Tulay Koc Delice; Arda Temizkalb; Ozgun Cem Ozgur; Belma Soydas Sozer (Materials Proceedings)
The unique magnetic, optical, and electrical properties of rare earth elements (REEs) have become essential in modern high technology. Considering the necessity of technology, efficient management and utilization of rare earth resources are of great importance. Even though there are more than 250 rare earth minerals around the world, the number of minerals that can be economically processed does not exceed three. Among these minerals, bastnaesite has a significant impact on scientific advancement and social progress. This project aims to contribute to the establishment of a sustainable supply chain for REE in Türkiye and Europe by conducting research and development activities to leverage the utilization of REEs found in our country. The primary objective of this project is to extract rare earth oxides from complex ore in the Eskişehir Beylikova region, which holds the largest reserve potential discovered in our country, and to refine these metal oxides to produce metals that can be used in magnet manufacturing. The project encompasses five main work packages over three years: project management, ore enrichment, solvent extraction-based purification, utilization of REOs and metals in additive materials, and magnet production.